Moral Values, Ethnicity Rights And Opportunities Of Women In John Irving’s The Cider House Rules (Journal of Namibian Studies : History Politics Culture, 2023)
John Irving a distinguished American novelist and short-story writer who established his reputation with one of his renowned novels The World According to Garp (1978); film (1982). He was born in March 2, 1942, Exeter, New Hampshire, U.S, As is characteristic of his other works, it is noted for its engaging story line, colourful characterizations, macabre humour, and examination of contemporary issues. Irving's career began at the age of 26 with the publication of his first novel, Setting Free the Bears (1968). The novel was reasonably well reviewed and gained a large readership. In the late 1960s, he studied with Kurt Vonnegut at the University of Iowa Writers' Workshop. Irving has been nominated for a National Book Award three times, winning in 1980 for The World According to Garp. In 2000, he won the Oscar for Best Adapted Screenplay for The Cider House Rules. In 2013, he won a Lambda Literary Award for In One Person. Internationally renowned, his books have been translated into more than thirty-five languages. A Prayer for Owen Meany is his best-selling novel, in every language.                 The Cider House Rules is essentially about moral values, ethnicity and abortions of women's right to have them. It is impossible to miss Irving's message, but his method of conveying it is ingenious in the extreme….Irving's mastery of plot and pacing has never been more engagingly on display. Yet the restrictions imposed by these skills are also evident. In the world according to Irving, characters are the passive victims of life. They are either children or childlike, dependent on forces beyond their control. They "wait and see' (an ongoing refrain in this novel), wondering, like Homer and Dr. Larch, "What is going to happen to me?" What literally happen to them, of course, are the tricks, sometimes macabre, visited upon them by their creator (23).